The Effects of Coffee Consumption on the Risk of Heart Failure - Wang, MSc, Yujie; Hu, MD, PhD, Gang (North American Journal of Medicine and Science, 2011)
Heart Failure (HF) has become a major public health problem in both developed and developing countries of the world. Although medical and surgical management has been improved, morbidity and mortality after onset of HF remain substantial; consequently, increasing attention has been drawn to preventing HF by management of lifestyle factors of HF. Coffee consumption is one of the lifestyle factors which has been linked to HF risk. Five prospective studies investigated the association between coffee consumption and the HF risk. However, the results of these studies were inconsistent. The authors conducted a review on the association between coffee consumption and HF risk in order to explore the possible reasons for the discordance and provide future research direction on this topic.